A VIEW ON LAWSUITS IN COVID-19 MEDICAL CASES: – FOREIGN PRACTICE - Mujović, Hajrija (Glasnik Advokatske komore Vojvodine, 2022)
The paper gives an overview of court cases with a medical background, which arose as a result of the Corona-19 pandemic. Most cases are initiated or terminated in the merits in civil proceedings. Proceedings are special and testify to disputes on various grounds and types of damage, whether they are directly conditioned by a pandemic or epidemiological measures or are only indirectly related to it. This is a foreign case law of developed European countries and the United States. Disputed situations are different and most often concern access to health care, preventive measures, testing, emergencies and other conditions from the aspects of the work of specialist services. Certainly, the crisis that has arisen cannot change the already existing legal institutes established by law and other rules that refer to the responsibility of health institutions and their employees. The crisis does not have that strength, but it brings certain features of diverse situations. This is shown by examples of lawsuits from the most recent court practice during the pandemic. In order to determine whether a doctor or other medical staff made a mistake, the court should take into account the specific working circumstances of each of them in the context of a pandemic. It is known that the position of each participant in the provision of health care is complex due to frequent crisis situations. Healthcare professionals face unusual risks in terms of the tasks they are given. The current legal regime of responsibility in health care provides answers, but it is not certain that all situations caused by the health crisis can be analyzed in the same way, especially due to the state of crisis and the dangers under which medical staff had to act. Crisis management can also create new legal situations.
Keywords: health crisis, Covid-19 litigation, medical damages, court decisions, foreign practice